SOME FEATURES OF THE TRANSFER OF RIGHTS TO COMMERCIAL SECRETS - Hayrapetyan, Arus (State and Law, 2022)
The article discusses the most common way to dispose commercial secrets - the transfer of commercial secrets and its methods. As the most common method of transferring commercial secrets, the transfer of commercial secrets by means of a contract is discussed in detail. The nature of the latter is revealed, issues of the relationship between the agreement on the transfer of commercial secrets and the license agreement are discussed and as a result, It is proposed under the agreement on the transfer of commercial secrets in the Civil Code RA to consider a not the licensing agreement, but an agreement that will be devoted to the transfer of commercial secrets and will reflect the essence and characteristics of the latters. It is proposed to call this agreement an agreement on the transfer of commercial secrets. Taking into account the presented considerations, it is proposed to rewrite and edit the Article 1166 of the Civil Code of RA under the title ´´ The Agreement on the transfer of commercial secrets ´´ with a broad regulation of the latter: the content of the proposed article is also given. The article also presents the signs and elements of the agreement on the transfer of commercial secrets, as defined by the author, and some other features of the latter.